Integrating DeepSeek into rural elderly services: opportunities, challenges, and adaptation strategies in Jilin Province, China - Hanjue, Wang; Vadeveloo, Thenmolli; Abd. Samad, Suhaimi (2025)
Given China's aging population and rural revitalization, artificial intelligence has provided a new approach to addressing the shortage of rural old-age resources. This study focuses on a village in Jilin Province, from the perspective of village cadres and township civil affairs cadres. By employing qualitative methods, including interviews with key informants (2 individuals) and focus groups (2 groups with a total of 10 participants), it investigates the process of implementing policies related to the DeepSeek system in old-age services. The study finds that grassroots managers believe DeepSeek enhances the understandability of policies through voice interaction to provide "plain language interpretation" of old-age subsidies and other policies; it precisely analyzes the needs of the elderly to improve service targeting; and it links county and township medical resources to conduct remote consultations, thereby strengthening resource integration. The challenges are mainly reflected in four contradictions: the elderly's insufficient digital literacy and limitations in dialect recognition; unstable village-level networks and the absence of a mechanism for sharing technical maintenance costs; the elderly's emotional aversion to "robot butlers" and privacy concerns; and the lack of effective standards to measure the improvement of service quality. In response to these challenges, it is suggested to develop dialect voice libraries to enhance technological inclusiveness; strengthen policy training for grassroots managers; establish resource integration mechanisms to deepen technological integration; customize technological functions based on rural needs; and build a scientific service quality evaluation system. The study shows that by advancing both technological adaptation and institutional innovation, DeepSeek can be effectively integrated into the rural old-age system, injecting new momentum into the old-age cause in Jilin Province.